2019
DOI: 10.1177/0261927x19886625
|View full text |Cite
|
Sign up to set email alerts
|

Voice Changes Meaning: The Role of Gay- Versus Straight-Sounding Voices in Sentence Interpretation

Abstract: Utterances reveal not only semantic information but also information about the speaker’s social category membership, including sexual orientation. In four studies ( N = 345), we investigated how the meaning of what is being said changes as a function of the speaker’s voice. In Studies 1a/1b, gay- and straight-sounding voices uttered the same sentences. Listeners indicated the likelihood that the speaker was referring to one among two target objects varying along gender-stereotypical characteristics. Listeners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(101 reference statements)
1
2
0
1
Order By: Relevance
“…Our findings align with previous work showing that people use stereotypes to interpret ambiguous expressions (Fasoli et al, 2020; Pexman & Olineck, 2002) and descriptions of target persons (Dunning & Sherman, 1997; Gawronski et al, 2003; Kunda & Sherman-Williams, 1993; Sagar & Schofield, 1980). Where this earlier work mainly focused on biased interpretations of the content of behavior descriptions (e.g., hitting somebody ; Kunda & Sherman-Williams, 1993), the present findings demonstrate how stereotypes affect interpretations of the generally applicable lexical category of quantity expressions.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings align with previous work showing that people use stereotypes to interpret ambiguous expressions (Fasoli et al, 2020; Pexman & Olineck, 2002) and descriptions of target persons (Dunning & Sherman, 1997; Gawronski et al, 2003; Kunda & Sherman-Williams, 1993; Sagar & Schofield, 1980). Where this earlier work mainly focused on biased interpretations of the content of behavior descriptions (e.g., hitting somebody ; Kunda & Sherman-Williams, 1993), the present findings demonstrate how stereotypes affect interpretations of the generally applicable lexical category of quantity expressions.…”
Section: Discussionsupporting
confidence: 91%
“…These findings connect to the dual-route approach to speech perception (Sumner, Kim, King, & McGowan, 2014), a model that delineates how receivers extract both linguistic (lexical meaning) and social (identity markers) information from speech. In that vein, Fasoli, Maass, Karniol, Antonio, and Sulpizio (2020) found that receivers interpreted gay- and straight-sounding speaker messages in a way that was consistent with identity marker stereotypes. Across four studies, receivers’ inferences about speakers’ voices were based on oversimplified and often stereotypical knowledge about the speakers’ identity (i.e., sexual orientation).…”
Section: Discussionmentioning
confidence: 79%
“…To our knowledge, this is the first research examining the interplay between voice and message that went beyond mere information processing and message interpretation (Fasoli et al., 2020; Nygaard et al., 2009). Moreover, it is the first cross‐cultural/linguistic research on the consequences of auditory gaydar.…”
Section: Discussionmentioning
confidence: 99%